2014
DOI: 10.1016/j.jcomdis.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Cross-situational statistically based word learning intervention for late-talking toddlers

Abstract: Purpose To explore the efficacy of a word learning intervention for late-talking toddlers that is based on principles of cross-situational statistical learning. Methods Four late-talking toddlers were individually provided with 7–10 weeks of bi-weekly word learning intervention that incorporated principles of cross-situational statistical learning. Treatment was input-based meaning that, aside from initial probes, children were not asked to produce any language during the sessions. Pre-intervention data incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 43 publications
0
47
1
2
Order By: Relevance
“…Other important language interventions address the underlying processes that support word learning-in particular, phonological knowledge, working memory, and attention (Alt et al 2012(Alt et al , 2014. One promising intervention with children from low-SES families found that targeting children's attention skills had a large impact on attention (as measured by event-related potentials) and led to gains in the children's receptive language abilities (Neville et al 2013).…”
Section: Enhancing Skills and Strategies For Language Acquisition: Camentioning
confidence: 99%
See 1 more Smart Citation
“…Other important language interventions address the underlying processes that support word learning-in particular, phonological knowledge, working memory, and attention (Alt et al 2012(Alt et al , 2014. One promising intervention with children from low-SES families found that targeting children's attention skills had a large impact on attention (as measured by event-related potentials) and led to gains in the children's receptive language abilities (Neville et al 2013).…”
Section: Enhancing Skills and Strategies For Language Acquisition: Camentioning
confidence: 99%
“…One promising intervention with children from low-SES families found that targeting children's attention skills had a large impact on attention (as measured by event-related potentials) and led to gains in the children's receptive language abilities (Neville et al 2013). Other studies have addressed the role of phonological or working memory training in word learning (Alt et al 2012(Alt et al , 2014Ellis et al 2015). However, most of the research investigating cognitive contributions to language acquisition involve language-impaired children from middle-and high-SES backgrounds.…”
Section: Enhancing Skills and Strategies For Language Acquisition: Camentioning
confidence: 99%
“…In addition, we need more research that explores causality via training studies (e.g. [31][32][33][34]). …”
Section: Introductionmentioning
confidence: 99%
“…Börn sem sein eru til máls eru mjög misleitur hópur en oftast er um að raeða börn á aldrinum 24 til 35 mánaða, sem eru sein í málþroska miðað við jafnaldra, og þá sérstaklega í tjáningu orða. Ekki er haegt að útskýra seinan málþroska barnanna með þáttum eins og heyrnarskerðingu eða einhverfu og þau eru of ung til að fá greininguna málþroskaröskun (Alt, Meyers, Oglivie, Nicholas og Arizmendi, 2014). Erfitt er að skilgreina barn sem er seint til máls fyrir tveggja ára aldur þar sem mikill fjölbreytileiki kemur fyrir í orðaforðatileinkun hjá börnum á því aldursskeiði (Tsybina og Eriks-Brophy, 2007).…”
Section: Börn Sem Eru Sein Til Málsunclassified